AIDS in adults 50 years of age and over: characteristics, trends and spatial distribution of the risk - Jordana de Almeida Nogueira; Antônia Oliveira Silva; Laísa Ribeiro de Sá; Sandra Aparecida de Almeida; Aline Aparecida Monroe; Tereza Cristina Scatena Villa (Universidade de São Paulo, 2014)
OBJECTIVE: to analyze the sociodemographic characteristics, epidemic trend and spatial distribution of the risk of AIDS in adults 50 years of age and over.METHOD: population-based, ecological study, that used secondary data from the Notifiable Disease Information System (Sinan/AIDS) of Paraíba state from the period January 2000 to December 2010.RESULTS: during the study period, 307 cases of AIDS were reported among people 50 years of age or over. There was a predominance of males (205/66, 8%), mixed race, and low education levels. The municipalities with populations above 100 thousand inhabitants reported 58.5% of the cases. There was a progressive increase in cases among women; an increasing trend in the incidence (positive linear correlation); and an advance in the geographical spread of the disease, with expansion to the coastal region and to the interior of the state, reaching municipalities with populations below 30 thousand inhabitants. In some locations the risk of disease was 100 times greater than the relative risk for the state.CONCLUSION: aging, with the feminization and interiorization of the epidemic in adults 50 years of age and over, confirms the need for the induction of affirmative policies targeted toward this age group.